Pendekatan Multidimensi dalam Penanganan Kekerasan Seksual Penyandang Disabilitas: Integrasi Psikologi, Spiritualitas, dan Hukum - Syifa, Syifa; Nurjannah, Nurjannah (Journal of Social Movements, 2024)
This study underscores the critical importance of adopting a multidimensional approach to address cases of sexual violence involving individuals with disabilities. By integrating psychological, spiritual, and legal perspectives, the research explores the behavioral patterns of perpetrators, the psychological and social impacts on victims, and systemic challenges within the legal framework. Employing a qualitative case study method, data were collected through in-depth interviews, legal document analysis, and social observations, followed by thematic analysis to identify recurring patterns and themes. The findings reveal that perpetrators with disabilities often employ emotional manipulation tactics, while victims suffer long-term trauma that significantly affects their mental health and social well-being. Innovative rehabilitation programs that combine psychological counseling with Islamic spiritual practices, such as emotional healing and self-reflection, demonstrate promising outcomes in facilitating recovery. However, substantial obstacles remain in ensuring justice and fairness for all stakeholders, particularly within the current legal system. This research contributes to the development of inclusive rehabilitation policies and strategies by highlighting the necessity of legal reforms, public education to combat stigma, and comprehensive psychosocial and spiritual support. The integration of psychological, spiritual, and legal dimensions offers a holistic framework for more effective interventions, ultimately promoting a more inclusive and equitable society.